Questioning Strategies in the English Classroom Interaction: An Effort in Improving EFL Learners’ Language Skills - Hulmayadi Rahman,; Arif Rahman,; Lalu Ari Irawan, (Journal of Language and Literature Studies, 2024)
Questioning strategies provide students with necessary springboards for communication. To encourage the students engagement and thinking in English Language learning, teachers’ need use different types of questioning strategies. Therefore, this research aims to explore the teacher’s questioning Strategies use in the English classroom interactions. The current study was focused on identifying the types of questioning strategies used by the English teachers in the English classroom interaction and finding out the teacher and students’ perception on using questioning strategy in the classroom interaction. This research used descriptive qualitative research. The technique of collecting data used by the researcher was observation and interview towards the English teachers. The instrument of this research are taken field note, transcription, interview and observation note. The results of the study shows that teachers employed several questioning strategies in the classroom, including rephrasing, simplification, repetition, decomposition, and probing. These strategies were used for various purposes based on the functions associated with each strategy. This study further indicates that based on the data interview most of the students agree with the implementation of questioning strategy during teaching and learning process.  Moreover, students believe that the uses of this strategy improve their understanding of the materials and recall the previous English material especially in the beginning of the class. In addition, all of teachers give positive response to use of questioning strategies practice in English class. This is because the questions presented in the class by teachers to students are very important to examine the students understand the material provided.